Optimising forage resources for goats through silvipastoral systems - Jamwal, Abhishek; Bishist, Rohit; Kishore, Kamal; Gupta, Shriya; Rana, Kashish (Indian Farming, 2026)
Goat farming plays a significant role in rural livelihoods, particularly for small and marginal farmers. However, fodder scarcity and degraded grazing lands pose challenges to sustainable goat production. Goats exhibit selective feeding behaviour, preferring browse materials over grasses, which influences their dietary intake and productivity. The silvipastoral system integrates trees, shrubs, and pasture, offering a sustainable solution to fodder shortages. This system not only enhances biomass availability but also improves soil fertility and livestock health. Various tree and shrub species, such as Leucaena leucocephala, Grewia optiva and Morus alba provide high-quality fodder across different agroclimatic regions.